2013
DOI: 10.4028/www.scientific.net/amr.690-693.2055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Hard Layers in Steel AISI 8620

Abstract: In the present study, identify the fracture toughness and strength adhesion of borided layers in Steel AISI 8620 by boriding dehydrated paste. The formation of the borided at a temperature range of 1173, 1223 and 1273 K for 4, 6 and 8 h. X-ray diffraction analysis revealed peak of FeB, Fe2B, MoB and CrB and The distribution of alloying elements was detected by means of energy dispersive Spectroscopy (EDS), the Fracture toughness of the layers is estimated at 15 and 30 um from surface using different loads inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In different boriding investigations it has been shown that the deposition of boron on the surface and the formation of a monolayer or bilayer of iron boride enhances materials properties; dependent on the technique of boriding and material study [7][8]. This type of technological advances and research provide the possibility of increasing the efficiency of treatment with boron by a different agent [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In different boriding investigations it has been shown that the deposition of boron on the surface and the formation of a monolayer or bilayer of iron boride enhances materials properties; dependent on the technique of boriding and material study [7][8]. This type of technological advances and research provide the possibility of increasing the efficiency of treatment with boron by a different agent [9][10].…”
Section: Introductionmentioning
confidence: 99%